Financial Anxiety, Financial Self-Efficacy, and Investment Decision-Making: A Mediation Perspective - Meliani Triana Puspitasari; Grace Indri; Alex Syauta; Nurlia Nurlia (Journal of Marketing Management and Innovative Business Review, 2026)
This study examines the relationship between financial anxiety, financial self-efficacy, and investment decision-making among individual investors in Indonesia. Grounded in Social Cognitive Theory and behavioral finance perspectives, the research investigates the mediating role of financial self-efficacy in explaining how financial anxiety influences investment behavior. A quantitative approach with an explanatory research design was employed, involving 150 retail investors selected through purposive sampling. Data were collected using structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with Smart-PLS software. The findings reveal that financial anxiety negatively and significantly affects investment decision-making and financial self-efficacy. In contrast, financial self-efficacy positively and significantly influences investment decision-making. Furthermore, the mediation analysis confirms that financial self-efficacy significantly mediates the relationship between financial anxiety and investment decision-making. These results indicate that higher financial anxiety weakens investors’ confidence in managing financial matters, which subsequently reduces the quality of investment decisions. The study contributes to behavioral finance literature by providing empirical evidence regarding the psychological mechanisms underlying investment behavior in emerging markets. Practically, the findings suggest that investment education programs should not only emphasize financial literacy but also strengthen psychological resilience and financial confidence among investors.